Nuevos cánones de arquitectura inka: investigaciones en el sitio de Tambokancha-Tumibamba, Jaquijahuana, Cuzco - Farrington, Ian S. (Pontificia Universidad Católica del Perú, 2012)
New Canons on Inka Architecture: Field Research at Tambokancha-Tumibamba Site, Jaquijahuana, CuzcoRecent excavations at the Tambokancha Complex by the Peruvian-Australian Jaquijahuana Project have revealed valuable discoveries about new inka architectonic structural patterns. The archaeological complex, to the west of the city of cuzco, is located on an alluvial fan and consists of high walls with stone and adobe masonry. These structures include, for example, towers and kallankas. Fortunately, this site has not been looted, although the adobe and stone blocks of the walls were dismantled for later constructions. In spite of this, the site shows a great monumentality. Tambokancha is one of the most atypical Inka sites architecturally. Among the most impressive of its architectonic characteristics is a cross shaped alignment in the complex core and its tumi (ceremonial knife) shaped general plan.